Ḥifẓ al-Dawlah as An Instrument for Realizing Maqāṣid al-Sharī’ah: A Maqāṣidī Exegetical Reading in The Indonesian Context - Arif Fakhrudin; Ahmad Thib Raya; M. Azizan Fitriana (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2026)
This article examines whether ḥifẓ al-dawlah should be classified as an independent objective of Islamic law or, more cautiously, understood as an institutional instrument for realizing established maqāṣid. The study focuses on Sūrah Quraysh [106], Q. al-Balad [90]:11–16, and supporting verses concerning security, welfare, justice, public trust, and defense. It employs qualitative library research and a maqāṣidī exegetical method through five stages: conceptual delimitation; selection of the Qurʾānic corpus; linguistic, contextual, and comparative exegesis; intratextual maqāṣid synthesis; and testing the proposition according to universality, normative certainty, public benefit, conceptual independence, and compatibility with justice. The findings show that Sūrah Quraysh links security and basic subsistence to moral responsibility, while Q. al-Balad makes liberation and the protection of vulnerable groups criteria of social legitimacy. Verses concerning public trust and justice further require political authority to protect citizens rather than merely preserve order. These findings support the state as an institutional prerequisite for protecting religion, life, intellect, family, and property, but do not conclusively establish ḥifẓ al-dawlah as a sixth independent maqṣad. In Indonesia, the concept is normatively defensible only when the object preserved is a just constitutional order, equal citizenship, and public welfare—not a particular government or regime.